Minor positive effects of health-promoting senior meetings for older community-dwelling persons on loneliness, social network, and social support - Gustafsson S (Dove Medical Press, 2017)
Susanne Gustafsson,1,2 Helene Berglund,1,3 Joel Faronbi,1,4 Emmelie Barenfeld,1,2,5 Isabelle Ottenvall Hammar1,2 1Frail Elderly Research Support Group (FRESH), Institute of Neuroscience and Physiology, Sahlgrenska Academy at Gothenburg University, 2Gothenburg University Centre for Ageing and Health (AgeCap), 3Institute of Health and Care Sciences, Sahlgrenska Academy at Gothenburg University, Gothenburg, Sweden; 4Department of Nursing Science, College of Health Science, Obafemi Awolowo University, Ile-Ife, Nigeria; 5Department of Occupational Therapy and Physiotherapy, Sahlgrenska University Hospital, Gothenburg, Sweden Objective: The aim of this study was to evaluate the 1-year effect of the health-promoting intervention “senior meetings” for older community-dwelling persons regarding loneliness, social network, and social support.Methods: Secondary analysis of data was carried out from two randomized controlled studies: Elderly Persons in the Risk Zone and Promoting Aging Migrants’ Capabilities. Data from 416 participants who attended the senior meetings and the control group at baseline and the 1-year follow-up in the respective studies were included. Data were aggregated and analyzed with chi-square test and odds ratio (OR) to determine the intervention effect.Results: The senior meetings had a positive effect on social support regarding someone to turn to when in need of advice and backing (OR 1.72, p=0.01). No positive intervention effect could be identified for loneliness, social network, or other aspects of social support.Conclusion: Health-promoting senior meetings for older community-dwelling persons have a minor positive effect on social support. The senior meetings might benefit from a revision to reinforce content focused on loneliness, social network, and social support. However, the modest effect could also depend on the lack of accessible social resources to meet participants’ identified needs, a possible hindrance for a person’s capability. This makes it necessary to conduct further research to evaluate the effect of the senior meetings and other health-promoting initiatives on social aspects of older community-dwelling people’s lives, since these aspects are of high importance for life satisfaction and well-being in old age. Keywords: aged, quality of life, health promotion, prevention, group intervention, evaluation studies